Do Rural Infrastructure Investments Benefit the Poor? Evaluating Linkages--A Global View, A Focus on Vietnam - Songco, Jocelyn A. (World Bank, Washington, DC, 2013)
What are linkages between rural infrastructure investments, and household welfare? In the past, most of the evaluations to assess the effectiveness of a project, focused on physical outputs, and success of project implementation. In recent years, more attention has been given to the impact of investments, particularly its effect on the poor, both in economic, and non-economic terms. The author presents findings from a survey of the existing literature on such impacts. Although evidence exists for improved household welfare from rural infrastructure investment, little evidence was found of studies that provided concrete linkages between specific investments in rural infrastructure, and increased welfare of the rural poor. This is due in part to the complexity, and oftentimes the concurrent nature of interventions, that make attributing welfare improvements, to a particular project, virtually impossible. The evidence is presented in this three-part paper. Part I gives examples of past, and current attempts to assess the impact of rural infrastructure projects, and provides suggestions for future evaluations. Part II discusses in detail some observed economic, and non-economic impacts on the poor, from different rural infrastructure interventions. Part III presents lessons learned from the literature on how to maximize the impact of rural infrastructure interventions on household welfare. Specific project, and country examples from the literature, and new data from a recent qualitative study in Vietnam, are presented as evidence for, and illustration of key ideas, and issues.